Analisis Tindak Tutur Lokusi dalam Video Kompilasi Cerita Rakyat 3in1 dari Betawi pada Channel Youtube Dongeng Kita - Putri Aji Rahayu; Laras Safitri; Asifah Salsadila; Muhammad Thoriq Akbar; Rindiati Amellia Fatikha; Wahyu Hari Winarno; Asep Purwo Yudi Utomo (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
As we already know, language is something that can never be separated from everyday life. One of the functions of language is communication, because humans are social creatures, communication is very important. A statement or utterance put forward by someone can be said to be a speech act. In linguistics, speech acts are included in the science of pragmatics, where there are several types of speech acts, one of which is locutionary speech acts. Locutionary speech acts are speech acts that only express meaning or state something. In this research, the author focuses more on locutionary speech acts in the video "Compilation of 3in1 Folk Tales from Betawi" on the Dongeng Kita YouTube channel. The aim of this research is to increase our knowledge about locutionary speech acts and find out what types of locutionary speech acts are included in the video “Kompilasi Cerita Rakyat 3in1 dari Betawi” on the Dongeng Kita YouTube channel. The approach used in this research is a qualitative descriptive approach and a paradigmatic approach. The data used in this research comes from the video "3in1 Compilation of Betawi Folk Tales" on the Dongeng Kita YouTube channel. The data collection technique we used in this research was listening to and noting the folklore video "3in1 Compilation of Betawi Folklore" on the Dongeng Kita YouTube channel. The benefit of conducting this research is that the public or readers can understand what locutionary speech acts are, and the examples. It is also hoped that it can provide an understanding that in folklore there is not only a story that can be enjoyed, but also many sayings that must be understood so that we can understand the entire content of what is being conveyed.